Customers’ perception of the determining factors of Visual Merchandising in Caracol points of sale in Holguin - González-Morera, Dayana; Díaz-Pompa, Félix; Gozález-Infante, Miguel Ángel; Fernández-Lara, Ania Yelina (Mercados y Negocios, 2023)
This research aims to analyze the perception of customers who visit points of sale on the determining elements of visual merchandising. The study is carried out under a quantitative and descriptive approach through a survey applied to a sample of 159 external customers, where it was found that there is a primarily positive perception. However, there are unfavorable factors such as the ambiance with music, the relevance of promotions, seasonality, and distribution of products. In conclusion, it is known that Caracol stores, although they use Visual Merchandising, have aspects that customers negatively perceive.